2017
DOI: 10.1016/j.joca.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

IκB kinase inhibition as a potential treatment of osteoarthritis – results of a clinical proof-of-concept study

Abstract: Inhibiting the NFκB signaling pathway is an attractive method to treat patients with signs and symptoms of OA. The preclinical work and the results of the phase 1 studies appeared promising for a full clinical development, however, the proof-of-concept study failed to show efficacy in a larger patient sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 14 publications
(10 reference statements)
1
25
0
Order By: Relevance
“…Positive efficacy trends in these studies motivated the undertaking of a Phase IIa POC trial (Identifier: NCT01598415). However, SAR-113945 failed to show efficacy in this larger patient sample size [ 127 ].…”
Section: Pre-clinical Development Of Ikkβ Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive efficacy trends in these studies motivated the undertaking of a Phase IIa POC trial (Identifier: NCT01598415). However, SAR-113945 failed to show efficacy in this larger patient sample size [ 127 ].…”
Section: Pre-clinical Development Of Ikkβ Inhibitorsmentioning
confidence: 99%
“…More challenging is the appropriate selection of patient subgroups to achieve the desired therapeutic efficacy. For example, the proof of concept study for SAR113945 failed to show any effect in the overall group of recruited study participants for the primary endpoint; however, post-study analysis demonstrated a statistically significant difference in a patient subgroup that had presented with synovial effusion at baseline [ 127 ]. Stratification of patient subgroups to identify those with a clear NF-κB-driven, inflammatory phenotype that would benefit from IKKβ inhibition may be one solution to this problem.…”
Section: Potential Reasons For the Lack Of Clinical Success Of Ikkmentioning
confidence: 99%
“…Parthenolide displays poor bioavailability and therefore has limited therapeutic application [ 142 ]. A new IKKβ inhibitor more recently developed by Sanofi-Aventis, SAR-113945, has been investigated in four different clinical trials in non-oncological patients, with initial promising results [ 143 ]. However, SAR-113945 has failed to demonstrate clinical efficacy in follow-on clinical trials, underscoring the challenge of striking an acceptable balance between efficacy and adverse side-effects [ 143 ].…”
Section: Therapeutic Targeting Of the Nf-κb Pathway In Cancermentioning
confidence: 99%
“…A new IKKβ inhibitor more recently developed by Sanofi-Aventis, SAR-113945, has been investigated in four different clinical trials in non-oncological patients, with initial promising results [ 143 ]. However, SAR-113945 has failed to demonstrate clinical efficacy in follow-on clinical trials, underscoring the challenge of striking an acceptable balance between efficacy and adverse side-effects [ 143 ]. Overall, the disappointing clinical performance of IKKβ inhibitors has considerably dampened the interest in this class of agents, and this trend is likely to continue in the future, as shown by the dramatic decline in the number of patent applications filed on these agents in recent years [ 107 ].…”
Section: Therapeutic Targeting Of the Nf-κb Pathway In Cancermentioning
confidence: 99%
“…A number of targets have been identified. For example, inflammatory modulators such as interleukins, [13] or the NF-κB pathway [14] have been identified as potential targets. Ion channels, such as TRPV1 [15] or voltage gated sodium channels, which are associated with pain, have also been investigated [16].…”
Section: Introductionmentioning
confidence: 99%